Partisipasi Masyarakat Kampung Kauman pada Tradisi Sekaten di Keraton Yogyakarta - Rosa Novia Sapphira; Eko Punto Hendro; Amirudin Amirudin (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
The existence of Sekaten tradition in The Yogyakarta Palace is one form of Javanese cultural heritage that is still preserved by the community until this day. According to the history, the emergence of Sekaten Tradition was not only to celebrate the birthday of the Prophet Muhammad, but also an initiation by Wali Sanga as an effort to spread the religion of Islam. The phenomenon of religious and cultural relations can be seen directly in the Sekaten Tradition held in Yogyakarta and its relation to the Kauman Yogyakarta Community. In fact, Sekaten with mystical traditional colors still exist in Kauman Village, where the majority of their people are identical with Islam and Muhammadiyah. They were accepted Sekaten's presence, even participated in those celebration. So that, the Sekaten tradition which always smells things that are forbidden by Islam, can continue to run well in every year.